2014
DOI: 10.1007/s13197-014-1689-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some extrusion variables on fermented maize-soybean blend

Abstract: The effects of feed moisture, sugar and temperature on extrusion of fermented maize-soybean blend was investigated. Fermentation caused a reduction in sectional expansion index from 1.342 to 1.244, bulk density from 0.5005 to 0.5002 g/cm3 and water absorption index (WAI) from 5.9 to 5.2 but increased specific volume from 7.13 to 7.15 cm3/g and water solubility index (WSI) from 1.2 to 1.7. Increase in feed moisture (20-35 %) reduced sectional expansion index, specific volume, bulk density and water solubility i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…This density increment might result in a sudden pressure drop in a lesser residence time creating highly expanded extrudes formation takes place. A similar trend of decrease in bulk density with temperature rise was also observed by Kaur et al [13]; Ojokoh et al [18].…”
Section: Bulk Densitysupporting
confidence: 86%
“…This density increment might result in a sudden pressure drop in a lesser residence time creating highly expanded extrudes formation takes place. A similar trend of decrease in bulk density with temperature rise was also observed by Kaur et al [13]; Ojokoh et al [18].…”
Section: Bulk Densitysupporting
confidence: 86%
“…Ojokoh et al. (2015) and, Chen and Rizvi (2006) also concluded that extrudates prepared with high moisture feeds were likely to collapse due to weaker structural integrity. Cho and Rizvi (2009) also reported that higher viscosity corresponds to higher gas holding capacity and further concluded that the extent of extrudate expansion is governed by gas retention capability which is related to the apparent viscosity of the extruder feed.…”
Section: Resultsmentioning
confidence: 99%
“…This result may be related to availability of more sugar in the system due to sugar content of grape pomace in addition to the fiber content. Ojokoh et al suggested that an increase in WSI with increasing sugar concentration was a sign of increased solubilization of starch.…”
Section: Resultsmentioning
confidence: 99%